Persistent problems of access to appropriate, affordable TB services in rural China: experiences of different socio-economic groups - Whitehead Margaret; Jun Gao; Tang Shenglan; Zhang Tuohong (BMC, 2007)
Abstract Background Large-scale Tuberculosis (TB) control programmes in China have been hailed a success. Concerns remain, however, about whether the programme is reaching all sections of the population, particularly poorer groups within rural communities, and whether there are hidden costs. This study takes a household perspective to investigate receipt of appropriate care and affordability of services for different socio-economic groups with TB symptoms in rural China. Methods Secondary analysis of Chinese National Household Health Survey for 2003: 40,000 rural households containing 143,991 individuals, 2,308 identified as TB suspects. Outcomes: use of services and expenditure of TB suspects, by gender and socio-economic position, indicated by household income, education, material assets, and insurance status. Results 37% of TB suspects did not seek any professional care, with low-income groups less likely to seek care than more affluent counterparts. Of those seeking care, only 35% received any of the recommended diagnostic tests. Of the 182 patients with a confirmed TB diagnosis, 104 (57%) received treatment at the recommended level, less likely if lacking health insurance or material assets. The burden of payment for services amounted to 45% of annual household income for the low-income group, 16% for the high-income group. Conclusion Access to appropriate, affordable TB services is still problematic in some rural areas of China, and receipt of care and affordability declines with declining socio-economic position. These findings highlight the current shortcomings of the national TB control programme in China and the formidable challenge it faces if it is to reach all sections of the population, including the poor with the highest burden of disease.